Pengembangan Komik Berbasis Cerita Rakyat Bengkulu untuk Mensukseskan Gerakan Literasi Sekolah di Sekolah Dasar - Neni Marlianti; Abdul Muktadir; Irwan Koto (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to make GLS a success in elementary schools by presenting comics based on Bengkulu folklore. This type of research is research and development (R&D). The subjects in this study were grade IV, V, and VI students at SDN 04 Bengkulu City. The object of this research is a product in the form of Bengkulu folklore comic media. The research data were analyzed using qualitative data analysis and quantitative data analysis. Quantitative data analysis technique uses quantitative descriptive. The data from the validation results were analyzed using Aiken's V. The results of the research on the validity of the material experts are 1) the content aspect, the index value of V is 1.00, the Aiken correlation coefficient shows that if it is in the range > 0.8 with the "very valid" category. 2) the language aspect, the V index value of 0.96 is said to be very valid. 3) the presentation aspect obtained an index value of V 1.00 so it is very valid or feasible. The results of the validity of the media expert, namely in terms of the graphic aspect, obtained a value of 0.97 which was categorized as very valid. The results of the material expert reliability test scores 1) the content aspect obtained a reliable value of 1 with a percentage of 100%, if the reliability coefficient if it ranges from 0.80 - 1 then the level of agreement is strong. 2). The language aspect obtained a reliable value of 0.9 with a percentage of 90%, so the level of agreement of opinion is strong. 3) the presentation aspect has a reliable value of 0.9 with a percentage of 90%, so the level of agreement is strong. The results of the media expert's reliability test assessment in terms of the graphic aspect obtained a reliable value of 0.8 with a percentage of 80% stated that there was a strong opinion agreement. So comics are really worth trying out. The results of the assessment of the student response questionnaires that answered yes as many as 28 people (93,3%) and answered yes and no as many as 2 people (6,67%) then the comics were very interesting.